Cronobacter: an emergent pathogen causing meningitis to neonates through their feeds. (1st June 2014) - Tall, Ben; Chen, Yi; Yan, QiongQiong; Gopinath, Gopal; Grim, Christopher; Jarvis, Karen; Fanning, Séamus; Lampel, Keith
The recognition of Cronobacter as a public health concern was raised when powdered infant formula (PIF) was linked to several neonatal meningitis outbreaks. It is an opportunistic pathogen that causes necrotising enterocolitis, infantile septicaemia, and meningitis which carries a high mortality rate among neonates. It has been also linked with cases of infection in adults and elderly. Over the past decade, much focus has been made on developing sensitive and specific characterisation, detection, and isolation methods to ascertain the quality of foods, notably contamination of PIF with Cronobacter and to understand its ability to cause disease. Whole genome sequencing has unveiled several putative virulence factors, yet the full capacity of the pathogenesis of Cronobacter has not yet been elucidated.